Gemella haemolysans Infection in Total Hip Arthroplasty. (9th May 2012) - Rose, Barry; Jeer, Parminder J. S.; Spriggins, Anthony J.
Abstract : Gemella haemolysans is a Gram-positive coccus and commensal of the upper respiratory tract and oral mucosa that rarely causes clinically important infections. There is only one previous report of this organism causing periprosthetic infection, in a total knee arthroplasty. We present a case of septic loosening of an uncemented total hip arthroplasty due to G. haemolysans, in an asplenic patient with insulin dependent diabetes mellitus. Treatment with two-stage revision has been successful at 7 years of follow-up.